Fetomaternal outcome in pregnancy with hepatitis E infection - Lewis, Preeti F.; Prasad, Sampada; Bavdekar, Nitin B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: HEV infection, a major public health concern, is known to cause large-scale epidemic and sporadic cases of acute viral hepatitis in developing countries. The infection occurs primarily in young adults and is generally mild and self-limiting; however, the case fatality rate is reportedly higher among pregnant women. Methods: Our study, a retrospective observational study, was conducted in a tertiary care center for over a period of 3 years (January 2017 to January 2020) to find out the fetal and maternal outcome in pregnant women with HEV infection. Results: A total of 38 antenatal cases with anti-HEV IgM-positive were included, and the maternal-fetal outcome was analyzed. The maternal mortality was 52.63 % especially during 3rd trimester and post-partum period, including 5 antenatal death. The most common maternal complication was acute fulminant hepatitis (39.5 %), DIC (36.8 %) and hepatic encephalopathy (31.6%). Prematurity (33.3% of total live births) and Still births (32.3 %) including 4 freshes still births were the commonest fetal complications noted. Conclusions: Our study shows that pregnant woman with acute viral hepatitis due to hepatitis E virus infection had a high mortality rate especially during 3rd trimester and post-partum period with poor obstetric and fetal outcome.